2022
DOI: 10.3390/pathogens11080907
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Accurate Detection of Gnomoniopsis smithogilvyi the Causal Agent of Chestnut Rot, through an Internally Controlled Multiplex PCR Assay

Abstract: The fungus Gnomoniopsis smithogilvyi is a significant threat to the production of sweet chestnut (Castanea sativa) nuts in Australia and worldwide. The pathogen causes nut rot, which leads to substantial production losses. Early and accurate diagnosis of the disease is essential to delineate and implement control strategies. A specific and sensitive multiplex PCR was developed based on the amplification of three barcode sequences of G. smithogilvyi. The assay reliability was enhanced by including the amplifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…In recent years, many studies have been conducted on the fungal pathogen G. smithogilvyi, mostly from countries where the chestnut is a significant commercial product [37][38][39][40]. In Portugal, Coelho and Gouveia [23] described G. smithogilvyi as the causal agent of brown chestnut rot for the first time, and it has been isolated from Portuguese chestnuts at frequencies ranging from 9.3% to 15.3% [23,25,41], but no studies have been previously reported on the morphology and ecophysiology of the isolates from Portugal and their The optimal tree is shown, as inferred using the neighbor-joining method [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many studies have been conducted on the fungal pathogen G. smithogilvyi, mostly from countries where the chestnut is a significant commercial product [37][38][39][40]. In Portugal, Coelho and Gouveia [23] described G. smithogilvyi as the causal agent of brown chestnut rot for the first time, and it has been isolated from Portuguese chestnuts at frequencies ranging from 9.3% to 15.3% [23,25,41], but no studies have been previously reported on the morphology and ecophysiology of the isolates from Portugal and their The optimal tree is shown, as inferred using the neighbor-joining method [34].…”
Section: Discussionmentioning
confidence: 99%
“…The TEF1-α sequence showed a higher diversity among isolates, with the Portuguese ones closer to those from Chile and Australia. Silva-Campos et al [40] developed and validated a multiplex PCR assay for G. smithogilvyi detection, and observed a very low level of genetic divergence between Australian isolates and those from other geographic origins.…”
Section: Discussionmentioning
confidence: 99%
“…The disease strongly curtails nut production in the areas where it is present, the pathogen irremediably compromising nut quality and organoleptic features, making the fruit tissue chalky and inedible [ 11 , 13 , 35 , 36 , 37 , 38 , 39 ]. As the fungus can live as an endophyte in latency in chestnut organs and tissues, the application of effective control measures is troublesome and relies only on post-harvest treatments: water curing, sterilization and chemicals application [ 10 , 16 ]. Since a chestnut grove is considered in all respects a forest, chemical treatments are prohibited for environmental reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the inconspicuous infections and the endophytic colonization of internal tree and nut tissue by G. castaneae , control measures against this harmful pathogen are, to date, limited and often ineffective [ 15 ]. Currently, most of the control methods rely on water curing, sterilization and the application of chemicals post-harvest [ 10 , 16 ]. However, the efficacy of these methods is strictly linked to disease severity, often being ineffective with high infection levels.…”
Section: Introductionmentioning
confidence: 99%
“…As for the qPCR method, LAMP does not require prior isolation of the pathogen in a culture medium to detect it in the infected tissues [18,50]. Recently, a multiplex PCR was developed by Silva-Campos et al [49] to detected the presence of G. smithogilvyi in chestnut fruit. This new method, based on the amplification of ITS, EF1-α, and beta-tubulin, is used as an internal control of the C. sativa gene petD in order to confirm that the negative results are due to the absence of G. smithogilvyi gDNA and not due to a reaction failure.…”
Section: Gnomoniopsis Smithogilvyi-biology Epidemiology Symptomatolog...mentioning
confidence: 99%